Os determinantes morfogenéticos da linguagem expressiva - Jorge, Elaine de Souza (1984)
The present work arises from a reinterpretation of expressive language determinants and organization in auditory deficience individuals. In this way, exposes to a critical analysis their conditions of structuring and acquiring a symbolic and essentially verbal system of communication. In a more particular way, this study evaluates the perspective of the discourse phonological organization in profound 'pre-Ianguage' deaf, as a process that surpasses the possibilities of a simple learning. Language - here as a semiotic process of a perceptuale expressive nature, and which is established by along phylogenetic and ontogenetic development - is so interpretaded by a new theoretical model of Human Cognition . Such model, based on Cibernetics, Logics, Linguistics and Genetics Epistemology's contributions, establishes morphogenetic frameworks, from which psychism is thought to be organized. So, this study appears under 2 (two) essential aims: 1°) to offer a theoretical basis to the dynamics and cognitive processing in which deaf subjects are involved during a verbal-symbolic system learning - according to an innatist hypothesis, of morphogenetic basis. 2st) to evaluate, by means of the writing expressive language presented on 'pre-language' profound deafs, F. Lo P. Seminerio's (1980) hypothesis 'of a morphogenetic memory in human species', from which, all the cognitive activity would be organized, coming to operate according to pre-established codestructures. In order to confirm the propositions that are established, and Empiric Verification is presented, by means of exploratory studies carried out with 6 (six) subjects. The results attest the existence of an audio-phonetic, selective and organizing boundary, also among deaf individuals. Thay also confirm that the circulating information is able to be linguistically treated, programmed and recovered, although do not exist the possibility of a feed-back mechanism to the system which is being developed. That is, although deaf subjects do not hear, they program audio-phonetically, and this program comes to be recovered or actualized thanks to the specialized resources and pedagogic techniques. Such results suggest a reappreciation of the usual psychopedagogic methods in this area, and offer a new orientation to the actual debates, concerning to the techniques and the instrumental.